2016
DOI: 10.1101/039123
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequential acquisition of virulence and fluoroquinolone resistance has shaped the evolution ofEscherichia coliST131

Abstract: Escherichia coli ST131 is the most frequently isolated fluoroquinolone-resistant (FQR) E. coli clone worldwide and a major cause of urinary tract and bloodstream infections. Although originally identified through its association with the CTX-M-15 extended-spectrum ␤-lactamase resistance gene, global genomic epidemiology studies have failed to resolve the geographical and temporal origin of the ST131 ancestor. Here, we developed a framework for the reanalysis of publically available genomes from different count… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(95 citation statements)
references
References 40 publications
(79 reference statements)
8
80
2
Order By: Relevance
“…This is supported by evidence that both drug-resistant (ST131) and drug-susceptible (ST73) lineages are equally successful in being maintained in this reservoir and that drug resistance as a whole in the population is not increasing, demonstrating that antibiotic resistance is not a primary driver of success or prevalence in this niche. In the case of ST131, this is supported by the findings of Ben Zakour et al (2016), who reported that virulence determinants were acquired before the emergence of the fluoroquinolone-resistant C clade (Ben Zakour et al 2016). According to this hypothesis, the primary forces shaping the population are not those within the hospital environment but are due to competition within the gut commensal niche in the broader human population, where antibiotic use is more sporadic than in the hospital population.…”
Section: Wwwgenomeorgsupporting
confidence: 75%
See 2 more Smart Citations
“…This is supported by evidence that both drug-resistant (ST131) and drug-susceptible (ST73) lineages are equally successful in being maintained in this reservoir and that drug resistance as a whole in the population is not increasing, demonstrating that antibiotic resistance is not a primary driver of success or prevalence in this niche. In the case of ST131, this is supported by the findings of Ben Zakour et al (2016), who reported that virulence determinants were acquired before the emergence of the fluoroquinolone-resistant C clade (Ben Zakour et al 2016). According to this hypothesis, the primary forces shaping the population are not those within the hospital environment but are due to competition within the gut commensal niche in the broader human population, where antibiotic use is more sporadic than in the hospital population.…”
Section: Wwwgenomeorgsupporting
confidence: 75%
“…3). The assignment of isolates to clades was confirmed by investigating six previously reported clade specific SNPs for B, C, C1, and C2 (Ben Zakour et al 2016). This confirmed our assignment of isolates to clades and revealed that the three fimH27 isolates in the B clade most likely belong to the B0 clade defined by Ben Zakour et al (2016).…”
Section: Genetic Characterization Of St131supporting
confidence: 69%
See 1 more Smart Citation
“…We obtained a curated list of 185 E. coli sequence type 131 (ST131) isolates from two recent studies (Price et al 2013;Petty et al 2014;Ben Zakour et al 2016), and a total list of 1216 S. pneumoniae isolates, which consisted of all isolates from the seven largest clusters in a longitudinal pneumococcal carriage study (Chewapreecha et al 2014). For each species, we applied a reference-based approach to generate whole-genome alignments from Illumina read data.…”
Section: G Application To Bacterial Sequence Analysismentioning
confidence: 99%
“…We used whole genome sequences from a recently emerged multidrug-resistant Escherichia coli clone, sequence type 131 (ST131) containing 185 isolates (Price et al 2013;Petty et al 2014;Ben Zakour et al 2016), and 1216 Streptococcus pneumoniae isolates in a longitudinal pneumococcal carriage study (Chewapreecha et al 2014), two species that are well known for horizontal transfer and recombination (Lorenz and Wackernagel 1994). For each dataset, and several subtypes or clades, we calculated sample diversity and correlation functions, and inferred the bulk population parameters (Table 2) by fittingP ð2Þ s;2 ðlÞ (see Appendix G for details of sequence analysis).…”
Section: Using Correlated Mutations To Infer Recombination Rates and mentioning
confidence: 99%